Pengendali Robot Tempat Sampah Menggunakan Smartphone Berbasis Boarduino - Andri Fadjria; Rakhmat Purnomo; Nur Rahman (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2019)
The cafeteria of Bhayangkara University, Greater Jakarta, has a problem that is a lot ofgarbage left by visitors to the canteen. Waste consists of plastic, paper, food scraps placedat the canteen table by visitors to the canteen. The location of the trash can is far from thevisitors, and the number of trash bins totaling 4 pieces, unable to accommodate the garbagefrom visitors to the canteen can get problems in environmental pollution for the future. Sohe made a study that produced a garbage bin robot with an industrial system 4.0, which isto assist the task of human work. With the aim of reducing the trash left by visitors to thecanteen and the convenience of visitors to put garbage on the robot. Using the protoypingmethod in the system of making garbage bins with the stages of collecting design processneeds, building prototypes, evaluating & repairing, producing a robot with a smartphonecontroller based on boarduino applications so that robots can work according to the needsexpected by researchers.